THE INCREASING OF OLIVE RIDLEY (Lepidochelys olivacea) POPULATION AND ITS CORRELATION WITH CONSERVATION ACTIVITY IN ALAS PURWO NATIONAL PARK BANYUWANGI-EAST JAVA - Priyo Suharsono Sulaiman; Ngurah Nyoman Wiadnyana (Indonesian Fisheries Research Journal, 2009)
One of the sea turtles nesting location in Indonesia that have a positive impact for olive ridley (Lepidochelys olivacea) captivity breeding is National Park Alas Purwo (TNAP) District of Banyuwangi East Java Province. Research was done by observation, interviews and descriptive analysis.